Effect of ozone application on the removal of pesticides from grapes and green bell peppers and changes in their nutraceutical quality. Issue 8 (26th August 2021) - Swami, Saurabh; Kumar, Birendra; Singh, Shashi Bala
Abstract: The present study evaluates the efficacy of ozonated water for the removal of pesticide residues in grapes and green bell peppers. Fruit fortified with pesticides (azoxystrobin, chlorothalonil, chlorpyrifos, cypermethrin, hexaconazole and methyl parathion) were subjected to 15 and 30 min aqueous ozone treatment. GC analysis of ozonated fruits showed a 48.67% to 96.95% decrease in pesticide residues of different pesticides. Methyl paraoxon, a toxic degradation product of methyl parathion, was detected in the ozonated water sample. To assess the effect of ozonation on the nutraceutical quality of fruits, the concentrations of eleven polyphenols and ascorbic acid were analyzed. The individual polyphenols showed different trend in 15 and 30 min treatment. Overall, there was an increase in the levels of all the polyphenols in grapes after 30 min ozonation treatment. In peppers, there was a net increase in quercetin, quercetin-3-O-glucoside, rutin and kaempferol in 30 min while other polyphenols were decreased. The ascorbic acid content of both the fruits was decreased by more than 70% upon ozonation. Thus, ozonation treatment was effective in pesticide removal. However, it changed the nutraceutical quality of grapes and green bell peppers.